2012
DOI: 10.1542/peds.2011-3634
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Osmotic Contrast Agent on Complete Meconium Evacuation in Preterm Infants

Abstract: Gastrografin application did not accelerate meconium evacuation, but the higher stool frequency during the first week of life had a beneficial effect on the time to full enteral feedings and later hospital stay; however, it may increase the necrotizing enterocolitis risk. Further investigations are needed with modified protocols, and the prophylactic use of Gastrografin cannot currently be recommended without further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 18 publications
2
56
0
3
Order By: Relevance
“…The observational study by Shim et al [5] (n = 83) was excluded from the final analysis. Thus, a total of 6 studies (n = 442) assessing different interventions (glycerine suppository/enema, saline enema, oral osmotic contrast agent) for meconium evacuation were eligible for inclusion in the analysis [24,25,26,27,28,29]. The characteristics of these studies are shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observational study by Shim et al [5] (n = 83) was excluded from the final analysis. Thus, a total of 6 studies (n = 442) assessing different interventions (glycerine suppository/enema, saline enema, oral osmotic contrast agent) for meconium evacuation were eligible for inclusion in the analysis [24,25,26,27,28,29]. The characteristics of these studies are shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2). Four of the 6 studies had TFF as the primary outcome [24,26,27,29], and those by Haiden et al [25] and Saenz de Pipaón Marcos et al [28] had TFF as the secondary outcome. We used the method of Hozo et al [30] to derive the mean and standard deviation from the median and range reported in the original article.…”
Section: Resultsmentioning
confidence: 99%
“…otro estudio evaluando el uso sistemático de supositorio de glicerina, con 54 casos randomizados, no muestra diferencias significativas pero una tendencia de mejor tolerancia en el grupo tratado 14 . La preocupación por estimular la eliminación de meconio y mejorar el aporte enteral persiste y un reciente estudio probó el aporte enteral de Gastrografin ® diluido 15 , que es una medida previamente utilizada para tratar un taponamiento meconial en prematuros extremos 10 . Este estudio aportó Gastrografin ® oral 9 ml por kilo en dilución 1:3, en las primeras 24 h de vida a menores de 1.500 g o 32 semanas.…”
unclassified
“…Este estudio aportó Gastrografin ® oral 9 ml por kilo en dilución 1:3, en las primeras 24 h de vida a menores de 1.500 g o 32 semanas. aunque hubo poca diferencia en el pasaje de meconio, tanto la tolerancia alimentaria como la duración de la hospitalización en cuidado intensivo, mejoraron significativamente en el grupo tratado; pero, aumentó el riesgo de ecn, lo que puede relacionarse con la alta osmolaridad del Gastrografin ® diluido (717 m mosm /L) 15 .…”
unclassified
See 1 more Smart Citation